Marine Natural Products: Promising Candidates in the Modulation of Gut-Brain Axis Towards Neuroprotection - Echeverria-Morgado, J (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
In recent decades, several neuroprotective agents have been provided in combating neuronal dysfunctions; however, no effective treatment has been found towards the complete eradication of neurodegenerative diseases. From the pathophysiological point of view, growing studies are indicating a bidirectional relationship between gut and brain termed gut-brain axis in the context of health/disease. Revealing the gut-brain axis has survived new hopes in the prevention, management, and treatment of neurodegenerative diseases. Accordingly, introducing novel alternative therapies in regulating the gut-brain axis seems to be an emerging concept to pave the road in fighting neurodegenerative diseases. Growing studies have developed marine-derived natural products as hopeful candidates in a simultaneous targeting of gut-brain dysregulated mediators towards neuroprotection. Of marine natural products, carotenoids (e.g., fucoxanthin, and astaxanthin), phytosterols (e.g., fucosterol), polysaccharides (e.g., fucoidan, chitosan, alginate, and laminarin), macrolactins (e.g., macrolactin A), diterpenes (e.g., lobocrasol, excavatolide B, and crassumol E) and sesquiterpenes (e.g., zonarol) have shown to be promising candidates in modulating gut-brain axis. The aforementioned marine natural products are potential regulators of inflammatory, apoptotic, and oxidative stress mediators towards a bidirectional regulation of the gut-brain axis. The present study aims at describing the gut-brain axis, the importance of gut microbiota in neurological diseases, as well as the modulatory role of marine natural products towards neuroprotection.